Combatting Islamophobia: A Reflection of an Anti-Racism Educator - Abdullah Najjar (Canadian Journal for New Scholars in Education, 2025)
Although Islamophobia has been rising in the West, educational institutions continue to struggle with incorporating anti-Islamophobia education into their curricula. Anti-Islamophobia education, which shares similarities with anti-racism education, can help challenge Islamophobia both within and beyond educational settings. Research on Islamophobia in the West, such as studies by Bakali (2016), Halabi (2021), Hossain (2017) and House (2012), predominantly focuses on students’ experiences and voices, often overlooking teachers’ perspectives on their efforts to combat Islamophobia in schools (Niyozov & Pluim, 2009). In this article, I use autoethnography as a methodology to reflect on my efforts to challenge Islamophobia at a secondary school in Quebec. I discuss a project I conducted with my students in my English as a Second Language (ESL) class. This project comprises two key dimensions: a conceptual aspect aimed at challenging racism and a technical component focused on teaching ESL. In this reflection, I concentrate on the issues regarding my practices as an anti-racist pedagogue rather than on my role as an ESL teacher. Although a few students were not comfortable discussing Islamophobia, most demonstrated a solid and critical understanding of it. They were brave enough to lead class discussions and offer different perspectives to challenge Islamophobia in their everyday life.